Anodes: Graphene‐Protected 3D Sb‐based Anodes Fabricated via Electrostatic Assembly and Confinement Replacement for Enhanced Lithium and Sodium Storage (Small 45/2015). Issue 45 (2nd December 2015) - Ding, Yuan‐Li; Wu, Chao; Kopold, Peter; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Graphene‐protected 3D Sb‐based anodes are designed and fabricated by Y. Yu and co‐workers using a facile electrostatic assembly and confinement replacement method. On page 6026, in this fabrication, commercial nickel foam is used as both a 3D growth substrate and as a reductant for converting Sb 3+ to Sb. When evaluated as binder‐free anodes for Li‐ion and sodium‐ion batteries, the obtained 3D electrodes exhibit remarkably enhanced lithium and sodium storage performance.